Sweet baby Jesus, the band who must not be named, and friends U can't trust: Disparaging, immoral and scandalous trademarks in the United States and the European Union. Issue 1 (3rd July 2019) - Dee, Juliet
ABSTRACT: This article will compare the ways in which the European Union's Office of Intellectual Property (EUIPO) and the US Patent and Trademark Office (PTO) have interpreted and applied their respective trademark laws, sometimes reaching opposite conclusions. Whereas EUIPO may not register trademarks considered to be "contrary to public policy and accepted principles of morality, " the US Supreme Court has struck down as unconstitutional a Lanham Act provision that had prohibited trademarks that were "disparaging, " and the US Court of Appeals for the Federal Circuit has struck down a Lanham Act provision that had prohibited trademarks that were "immoral" or scandalous." After analyzing the legal arguments in trademark litigation in both Europe and the United States, this article concludes that the US Supreme Court should affirm the Federal Circuit's decision in In re Brunetti because it is more efficient to "allow the marketplace to decide" rather than place the onus of keeping up with changes in cultural values on PTO examiners. This article assumes that the European Union will continue in its efforts to prevent registration of trademarks containing hate speech or racial slurs.